2004
DOI: 10.1161/01.res.0000129254.25507.d6
|View full text |Cite
|
Sign up to set email alerts
|

What Mechanisms Underlie Diastolic Dysfunction in Heart Failure?

Abstract: Abstract-Abnormalities of diastolic function are common to virtually all forms of cardiac failure. However, their underlying mechanisms, precise role in the generation and phenotypic expression of heart failure, and value as specific therapeutic targets remain poorly understood. A growing proportion of heart failure patients, particularly among the elderly, have apparently preserved systolic function, and this is fueling interest for better understanding and treating diastolic abnormalities. Much of the attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
345
1
15

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(367 citation statements)
references
References 181 publications
6
345
1
15
Order By: Relevance
“…Several mechanisms may be postulated for obesity-associated defects in Lep/ Lep cardiac contractility and intracellular Ca 2+ handling. It has been reported that prolonged duration of relaxation may simply be a consequence of impaired SERCA and Na + /Ca 2+ exchanger function [43]. This is supported by enhanced SERCA oxidative modification, reduced 45 Ca 2+ uptake and slowed intracellular Ca 2+ clearing rate (τ) in Lep/Lep mouse cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may be postulated for obesity-associated defects in Lep/ Lep cardiac contractility and intracellular Ca 2+ handling. It has been reported that prolonged duration of relaxation may simply be a consequence of impaired SERCA and Na + /Ca 2+ exchanger function [43]. This is supported by enhanced SERCA oxidative modification, reduced 45 Ca 2+ uptake and slowed intracellular Ca 2+ clearing rate (τ) in Lep/Lep mouse cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…2001; Kass et al. 2004). Studies in human volunteers reported that invasive measures of LV pressure and indexes of LV untwist are related to parameters of early diastolic filling (Burns et al.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 2 decades, the syndrome of heart failure with preserved ejection fraction (HFpEF) received a lot of attention 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. However, little therapeutic progress was made 20, 21, 22, 23, 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…As a whole, HFpEF has been extensively reviewed 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. The present review focuses on 4 commonly encountered clinical phenotypes of HFpEF and their comorbid conditions (Figure).…”
Section: Introductionmentioning
confidence: 99%